AB0068 Structural Characteristics of Polysaccharides Influence Viscosupplementation Efficacy in Osteoarthritis. (15th July 2016) - Castro, R.R.; Nunes, R.M.; Silva, C.M.; Cunha, P.L.; Paula, R.C.; Feitosa, J.P.; Girão, V.C.; Pompeu, M.L.; Leite, J.A.D.; Rocha, F.
Abstract : Background: Intra-articular (i.a) injection of a purified Guar gum (GG) solution or hydrogel provided analgesia similar to that of Hylan G-F20 in experimental osteoarthritis (eOA) suggesting that rheology is not crucial to viscosupplements. Objectives: Evaluate the effect of purified GG (DGG), sulfated (DGGSU) of oxidized (DGGOX) GG on pain and cartilage damage in eOA Methods: GG was oxidated with a n-oxil-2, 2, 6, 6-tetra metilpiperidina (TEMPO) reagent or subjected to sulfation to produce carboxylated and sulphate groups. Rats subjected to anterior cruciate ligament transection (ACLT) of the knee received 100 μg GG, sulfated or oxidized GG or vehicle (NT) i.a. at day 4 to 7 after ACLT. Joint pain was recorded using the articular incapacitation test. A group received GG weekly or vehicle from day 7 to 70 and joint damage assessed by histology and biochemically, measuring hondroitin-sulfate (CS) cartilage content (μg/mg) and Mw of CS through PAGE. Results: FT-InfraRed spectra of DDGSU and DDGOX were different from protein free DGG. DGGSU has a new intense band at 1262 cm –1, due to S=O. Spectral difference occurs in DGGOX but not DGG and a C=O stretching is present in DGGOX spectrum (COOH group). 13 C NMR spectrum of DGGOX and DGG revealed absence of the signal at 63.7 ppm present in DGG and two new signals at 177.5 and 177.8 ppm. Absence of the signal from C-6 of free mannose indicates it was substituted in the oxidation. The new signals are from C=O group from COOH. 1 H- 13 C HSQC spectra exhibited a shift to a lower d value of the proton H-1 from mannose residue in DGGOX, indicating substitution at C-6 from mannose. New signals at 70.3, 75.6, and 100.5 ppm were observed in 13 C NMR spectrum of sulfated gum due to the insertion of sulfate group in the primary carbon (C-6). All derivatives show lower molar mass than the original guar gum. DGG Mw =3.9 x 10 6 g/mol, DGGOX and DGGSU, 2.6 x 10 6 and 2.8 x 10 6 g/mol, respectively. DGGOX has the lowest intrinsic (2.2 dL/g) and apparent viscosity (9.0 mPa s).DGG exhibits the highest values ([h] =6.2 dL/g and happ =58 mPa s). Intermediate values are obtained for DGGSU ([h] =4.9 dL/g and happ =39 mPa s). GG significantly reduced joint pain, as compared to vehicle whereas oxidat ion or sulfation of GG abrogated GG analgesia. GG also prevented the increase in both CS content (43.8±4.7 μg/mg) and Mw (mobility: 1.18 ±0.03), as compared to NT (p<0.001). GG also significantly prevented joint damage at histopathology (median =7; range 2.5 - 18), as compared to NT (p<0.05). Conclusions: The structural integrity of GG is crucial to its analgesia. Intra-articular polysaccharides can be analgesic and chondroprotective regardless of being water-soluble. Acknowledgement: Supported by grants 302218/2014–9 and 459334/2014–0 from CNPq-Brasil). Disclosure of Interest: None declared